Assessment of social support in relation to the risk of falls among elderly - Soares, Cristiane Regina; Okuno, Meiry Fernanda Pinto (Revista de Enfermagem da UFPI, 2024)
Objective: To assess social support in relation to the risk of falls. Method: A quantitative and cross-sectional study conducted in an outpatient clinic specializing in elderly care in the city of São Paulo (SP). The sample consisted of 117 elderly individuals, between March and November 2019. The Downton Risk of Falls and Medical Outcomes Study scales were used to measure the data. The Mann-Whitney test was used to assess the risk of falls, with social support considered at a significance level of 5% and a confidence interval of 95%. Results: There was a significant correlation between the risk of elderly individuals falling and social support in the affective dimensions (p=0.0028) and positive social interaction (p=0.0017). A high level of social support perceived by the elderly reduces the risk of falls by 4%. Furthermore, in the affective, emotional/informational dimensions, and positive social interaction, the probability of falls is reduced by 28%. Conclusion: In short, these results have relevant implications for nursing practice, since elderly people who are at high risk of falls have a lower perception of social support, thus, it is important to direct actions toward prevention and health promotion for this population.